The structure of mushroom polysaccharides and their beneficial role in health. Issue 10 (8th September 2015) - Huang, Xiaojun; Nie, Shaoping
Abstract : The polysaccharide contained in mushroom is regarded as one of the primary bioactive constituents and is beneficial for health. Abstract : Mushroom is a kind of fungus that has been popular for its special flavour and renowned biological values. The polysaccharide contained in mushroom is regarded as one of the primary bioactive constituents and is beneficial for health. The structural features and bioactivities of mushroom polysaccharides have been studied extensively. It is believed that the diverse biological bioactivities of polysaccharides are closely related to their structure or conformation properties. In this review, the structural characteristics, conformational features and bioactivities of several mushroom polysaccharides are summarized, and their beneficial mechanisms and the relationships between their structure and bioactivities are also discussed.